2000
DOI: 10.1007/s002230001108
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte Differentiation in Human Osteoarthritis: Expression of Osteocalcin in Normal and Osteoarthritic Cartilage and Bone

Abstract: Osteocalcin (OC), which is a marker of the mature osteoblasts, can also be found in posthypertrophic chondrocytes of the epiphyseal growth plate, but not in chondrocytes of the resting zone or in adult cartilage. In human osteoarthritis (OA), chondrocytes can differentiate to a hypertrophic phenotype characterized by type X collagen. The protein- and mRNA-expression pattern of OC was systematically analyzed in decalcified cartilage and bone sections and nondecalcified cartilage sections of human osteoarthritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 47 publications
4
88
0
6
Order By: Relevance
“…Regarding the treatment of articular cartilage defects, the engineered chondrocytes must arrest maturation processes, because abnormally matured hypertrophic chondrocytes, expressing COL10A1, mineralize cartilage matrix to cause pathological conditions such as osteoarthritis (OA) (22)(23)(24). This is a major problem of cartilage tissue engineering in an in vitro culture system, where MSCs rapidly express COL10A1 in a monolayer or pellet culture before the cells express hypertrophic phenotypes, suggesting that the mechanism by which MSCs induce type X collagen expression in vitro is different from that in chondrogenesis in vivo (25,26).…”
Section: Although Bone Morphogenic Protein (Bmp) Signaling Promotes Cmentioning
confidence: 99%
“…Regarding the treatment of articular cartilage defects, the engineered chondrocytes must arrest maturation processes, because abnormally matured hypertrophic chondrocytes, expressing COL10A1, mineralize cartilage matrix to cause pathological conditions such as osteoarthritis (OA) (22)(23)(24). This is a major problem of cartilage tissue engineering in an in vitro culture system, where MSCs rapidly express COL10A1 in a monolayer or pellet culture before the cells express hypertrophic phenotypes, suggesting that the mechanism by which MSCs induce type X collagen expression in vitro is different from that in chondrogenesis in vivo (25,26).…”
Section: Although Bone Morphogenic Protein (Bmp) Signaling Promotes Cmentioning
confidence: 99%
“…Th is protein is a marker of bone formation and turnover. Its role in the pathology of osteoarthritis is still not fully known, but former studies reported an increased release of osteocalcin by subchondral bone [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, chondrocyte maturation has been implicated to be deeply involved in the pathogenesis of osteoarthritis. In articular cartilage of osteoarthritis patients, pathologic expression of type X collagen (COL10) and other differentiation markers, including annexin VI, alkaline phosphatase, osteopontin, and osteocalcin, have been reported, [16][17][18][19][20] indicating that the osteoarthritis articular cartilage cannot maintain the characteristics of the permanent cartilage, but adds those of the embryonic or growth plate cartilage. A mouse genetic study found the induction of Runx2, an essential transcription factor for chondrocyte hypertrophy, [21,22] in articular chondrocytes during osteoarthritis progression under mechanical stress, which led to cartilage degradation and osteophyte formation through the chondrocyte maturation and MMP production [23,24].…”
Section: Hiroshi Kawaguchi*mentioning
confidence: 99%